2016
DOI: 10.1111/jcmm.12949
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for decreased induction of class IB PI3‐kinases expression by MIF inhibitors

Abstract: Macrophage migration inhibitory factor (MIF) is a master regulator of proinflammatory cytokines and plays pathological roles when not properly regulated in rheumatoid arthritis, lupus, atherosclerosis, asthma and cancer. Unlike canonical cytokines, MIF has vestigial keto‐enol tautomerase activity. Most of the current MIF inhibitors were screened for the inhibition of this enzymatic activity. However, only some of the enzymatic inhibitors inhibit receptor‐mediated biological functions of MIF, such as cell recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…MIF participates as a proinflammatory cytokine in both innate and adaptive immune responses, contributing to the pathogenesis of inflammatory, metabolic, autoimmune, and allergic diseases. Of note, MIF plays a pivotal role in activating the expression of PI3Kγ regulatory (p101) and catalytic subunits (p110) [ 59 ]. In turn, increased PI3Kγ activity is responsible for IL-13-mediated contraction of airway smooth muscle (ASM) cells, the underlying mechanism of AHR induced by allergen sensitization or cytokines in asthma [ 59 63 ].…”
Section: Pi3kγ Role In Respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…MIF participates as a proinflammatory cytokine in both innate and adaptive immune responses, contributing to the pathogenesis of inflammatory, metabolic, autoimmune, and allergic diseases. Of note, MIF plays a pivotal role in activating the expression of PI3Kγ regulatory (p101) and catalytic subunits (p110) [ 59 ]. In turn, increased PI3Kγ activity is responsible for IL-13-mediated contraction of airway smooth muscle (ASM) cells, the underlying mechanism of AHR induced by allergen sensitization or cytokines in asthma [ 59 63 ].…”
Section: Pi3kγ Role In Respiratory Diseasesmentioning
confidence: 99%
“…Of note, MIF plays a pivotal role in activating the expression of PI3Kγ regulatory (p101) and catalytic subunits (p110) [ 59 ]. In turn, increased PI3Kγ activity is responsible for IL-13-mediated contraction of airway smooth muscle (ASM) cells, the underlying mechanism of AHR induced by allergen sensitization or cytokines in asthma [ 59 63 ]. IL-13 receptor and PI3Kγ are both expressed in ASM cells, in which they control contractility by regulating Ca 2+ oscillations [ 64 ].…”
Section: Pi3kγ Role In Respiratory Diseasesmentioning
confidence: 99%
“…Interestingly, reports suggest a temporal diverse expression of the regulatory subunits with an induced upregulation of p101 in immune cells and heart tissues while p87 protein levels remained unchanged [33,112]. Most recently, it was demonstrated that macrophage migration inhibitory factor (MIF) up-regulates the expression of p101 in THP-1 monocytes and HL60 neutrophil-like cells [113]. Hence, it is tempting to consider p101 as part of an inducible PI3Kγ but further work needs to explore this possibility.…”
Section: Biological Functions Of Pi3kγmentioning
confidence: 99%
“…11,12 Chemical modifications, site-directed mutagenesis, and recent structural modeling studies indicate that CD74 activation is dependent on residues at the interface between two subunits, outside the catalytic cavity of the MIF proteins. 9,1113 Recent mechanistic insights into the MIF-1-induced activation of CD74 showed that the activation process is dynamically controlled by an allosteric site that is found on one side of the solvent channel. 14 Whether a similar allosteric site exists for MIF-2 has yet to be explored.…”
mentioning
confidence: 99%